1986
DOI: 10.1111/j.1365-3113.1986.tb00539.x
|View full text |Cite
|
Sign up to set email alerts
|

The Gomphaeschninae (Odonata: Aeshnidae): new fossil genus, reconstructed phylogeny, and geographical history

Abstract: Three new species of fossil Anisoptera [dragonflies) are reported from Tiffanian (Late Palaeocene) sediments of the Paskapoo Formation, near Red Deer, Alberta, Canada. The three species are all assigned to the new genus Altoaeschna, which is classified in the subfamily Gomphaeschninae.Phylogenetic analysis of gomphaeschnine wing venation suggests that the subfamily is paraphyletic, with derived gomphaeschnines such as Boyeria and Linaeschna more closely related to the Brachytroninae and Aeshninae than are othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
3

Year Published

1991
1991
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 9 publications
0
20
0
3
Order By: Relevance
“…The new fossil taxon has a relatively rare combination of relatively plesiomorphic characters that precludes an attribution to the more derived subgroups within Aeshninae, such as Rspl and Mspl parallel to IR2 and MA respectively (not strongly curved, but with two rows of cells between Rspl and IR2 and between Mspl and MA), IR2 unforked, and no aeshnid bulla of MA developed (Bechly et al 2001 (Nel et al, 1996) that was originally referred to the genus Allopetalia). All these genera were originally classified in the same subfamily Gomphaeschninae (e.g., Tillyard & Fraser 1940;Wighton & Wilson 1986;Bridges 1994;Nel et al 1994), but later shown to belong to different clades within Aeshnidae. However, the phylogenetic analysis of fossil evidence and wing venation (Bechly 1996(Bechly , 2002Bechly et al 2001), comparative recent morphology of genitalia (von Ellenrieder 2002;Peters & Theischinger 2007), and genetic evidence (Carle et al 2015) lead to incongruent results concerning the placement of the mentioned four subgroups or even their generic composition.…”
Section: Discussionmentioning
confidence: 99%
“…The new fossil taxon has a relatively rare combination of relatively plesiomorphic characters that precludes an attribution to the more derived subgroups within Aeshninae, such as Rspl and Mspl parallel to IR2 and MA respectively (not strongly curved, but with two rows of cells between Rspl and IR2 and between Mspl and MA), IR2 unforked, and no aeshnid bulla of MA developed (Bechly et al 2001 (Nel et al, 1996) that was originally referred to the genus Allopetalia). All these genera were originally classified in the same subfamily Gomphaeschninae (e.g., Tillyard & Fraser 1940;Wighton & Wilson 1986;Bridges 1994;Nel et al 1994), but later shown to belong to different clades within Aeshnidae. However, the phylogenetic analysis of fossil evidence and wing venation (Bechly 1996(Bechly , 2002Bechly et al 2001), comparative recent morphology of genitalia (von Ellenrieder 2002;Peters & Theischinger 2007), and genetic evidence (Carle et al 2015) lead to incongruent results concerning the placement of the mentioned four subgroups or even their generic composition.…”
Section: Discussionmentioning
confidence: 99%
“…Their pre‐adapted cold‐hardy aquatic larval stage must have buffered certain odonates from ever more extreme temperature fluctuations post‐Eocene (Archibald et al ., ), and these detritus‐based groundwater‐fed ecosystems are known to offer an unparalleled buffering effect even during extreme environmental deterioration leading to mass extinctions (Robertson et al ., ). Although fossil preservation is low in the humid erosional forests of Eastern/central NA (Dillon & Robinson, ), there are very few stem group Odonata (extinct lineages) in NA compared to other parts of the globe and the oldest Odonata fossil evidence from NA that we could find dates to around the Palaeocene ~ 60 Ma (Wighton & Wilson, ). Thus, we cannot rule out relatively lower extinction rates as a contributing factor to the high levels of forested freshwater diversity maintained here for aeons.…”
Section: Discussionmentioning
confidence: 99%
“…Individual plant taxa from the site have been described by Stockey and Crane (1983), Crane and Stockey (1985), Pigg and Stockey (1991), Hoffman and Stockey (1994). Faunal remains include freshwater molluscs, insects (Kevan and Wighton, 1981;Wighton, 1982;Wighton and Wilson, 1986), fish (Wilson, 1980;Williams and Wilson, 1988;Wilson and Williams, 1991;Murray, 1994), amphibians and reptiles (M.V.H. Wilson, University of Alberta, personal communication), and mammals (Fox, 1990).…”
Section: Methodsmentioning
confidence: 99%